Ecological restoration of an oak woodland in Kansas informed with remote sensing of vegetation dynamics - Galgamuwe Arachchige, Pabodha Galgamuwa (Kansas State University, 2017)
Recurrent, landscape-level fires played an integral part in the development and persistence of eastern oak (Quercus spp.) forests of the United States. These periodic surface fires helped secure a competitive position for oaks in the regeneration pool by maintaining a desirable species composition and forest structure. This historical fire regime was altered with the European settlement of North America, and fire suppression within forestlands became a standard practice since 1930s. With decades of fire suppression, mature oak-dominated woodlands have widely converted to shade-tolerant tree species. Prescribed fire has successfully been used to enhance oak regeneration in eastern forests. However, oak woodland restoration within the forest-prairie ecotone of the Central plains has not been systematically studied. Fuel beds under shade-tolerant species are often less conducive to fire. Therefore, monitoring fuel loading (FL) and its changes are essential to inform management decisions in an oak regeneration project. Rapid expansion of eastern redcedar (Juniperus virginiana/ERC) is another ecological issue faced by land managers throughout North America’s midcontinent forest-prairie ecotone. Hence, it is worthy to monitor ERC expansion and effects on deciduous forests, to inform oak ecosystem restoration interventions within this region. Therefore, the main objectives of this dissertation were three-fold: (1) understand the effects of prescribed burning and mechanical thinning to encourage oak regeneration; (2) investigate the initial effects of an oak regeneration effort with prescribed fire and mechanical thinning on FL; and (3) monitor the spatio-temporal dynamics of ERC expansion in the forest-prairie ecotone of Kansas, and understand its effects on deciduous forests. The first two studies were conducted on a 90-acre oak dominated woodland, north of Manhattan, Kansas. The experimental design was a 2 (burn) x 2 (thin) factorial in a repeated measures design. The design structure allowed four treatment combinations: burn only (B), thin only (T), burn and thin combined (BT), and a control (C). Burning and thinning treatments were administered in spring 2015. Changes in the FL estimates after the burn treatment revealed that the BT treatment combination consumed more fuel and burned more intensely compared to the B treatment. This observation was reflected in vegetation responses. The thinning reduced the canopy cover significantly, but under enhanced light environments, both oaks and competitive species thrived when no burn was incorporated. In contrast, burn treatments controlled the competitive vegetation. Hence, the most promising results were obtained when both fire and thinning were utilized. The remote sensing study documented the expansion of ERC in three areas of eastern Kansas over 30 years. The use of multi-seasonal layer-stacks with a Support Vector Machines (SVM) supervised classification was found to be the most effective approach to map ERC distribution. Total ERC cover increased by more than 6000 acres in all three study areas investigated in this study between 1986 and 2017. Much of the ERC expansion was into deciduous woodlands. Therefore, ERC control measures should be incorporated into oak woodland restoration efforts within the forest-prairie ecotone of Kansas.
Keywords: Prescribed fire; Eastern redcedar; Support Vector Machines; Oak regeneration; Fuel loading; Landsat